New record of Cestrum mortonianum (Solanaceae) and description of a new variety in the Pacific slope of Mexico - Cuevas, Ramón; Montero, Juan Carlos (Instituto de Ecología, A.C., 2011)
We present a review of the geographic distribution of Cestrum mortonianum, as well as a description and an illustration of a new variety from the Sierra de Manantlan. The features that differentiate this variety from C. mortonianum var. mortonianum, and from C. tomentosum and C. pacificum -all of which share the presence of branched pubescence - are also discussed. A key to distinguish the Mexican species of Cestrum whith this indumenta is provided.